Resepsi Khalayak Tentang Kebangkitan Sepak Bola Nasional Dalam Konten Youtube Bung Binder Dan Bung Ropan - Azis, Abdul; Utami, Sinta Dwi (Jurnal Ilmiah Kanderang Tingang, 2025)
This study aims to understand how audiences interpret the narrative of the revival of national football built by Content Creator Bung Binder and Bung Ropan on the YouTube platform. This research uses a qualitative approach with Stuart Hall's encoding decoding model reception analysis method. This method is used as an analysis instrument to map the audience's meaning position, namely dominant-hegemonic, negotiation, and opposition positions. The results showed that the narrative of the revival of national football built by Bung Binder and Bung Ropan was accepted with various meanings by the audience. The majority of informants are in a negotiation position, where they accept the narrative of the revival of national football built by Bung Binder and Bung Ropan, but remain critical of opinions or views that do not match their personal judgment. Other research results show that content creators Bung Binder and Bung Ropan play an important role in building the narrative of the rise of national football through their content on the YouTube platform.